Desenvolvimento rural na Amazônia brasileira: determinantes, níveis e distribuição regional na década de 2000 - Lobão, Mário Sérgio Pedroza (2018)
From the 1960s to the 2000s, the development of the Brazilian Amazon was marked by two main moments. The first was linked to development policies, in which it was based on the valorization of large private capital projects with the granting of credit by the government, for stimulating population densities through rural settlements and for the creation of several federal highways to integrate social and economically the Amazon to the rest of the country. This model lasted from the 60's and 80's in the military period. The second moment arises from the 90s with the promotion, both nationally and internationally, of environmental discussions around economic explorations. Here were adopted conservationist development policies, where environmental sustainability becomes the main focus on the public schedule. Therefore, the previous model is broken and a new course of development is assumed. It is against these claims that we sought to understand how the process of rural development behaved along these conjuncture and structural changes in the region of the Brazilian Amazon. It was decided to analyze the determinants, levels and regional distribution of rural development in the municipalities of the region under study in the 2000s, which is due to the historical accumulation of the public development policies adopted in the Amazon. The research has a main quantitative character, in which the rural development was measured through an analytical index composed of the dimensions sociodemographic, environmental and economic. The Factorial Analysis by Principal Components was used as a methodological resource for the formation of determinants of rural development and subsequent creation of the Rural Development Index (RDI), verifying the levels of development of the states and municipalities. With the production of the RDI, still is visualized the presence of spatial patterns of rural development by means of Exploratory Spatial Data Analysis. The main results showed that the Brazilian Amazon is still a region territorially rural, in which it has some poles urbanized as was the case of state capitals and some middling municipalities. It was also noted that the best social and economic indicators were found in the states of Pará, Rondônia and Tocantins, but the worst environmental indicators. On the other hand, it was in the states of Acre, Amapá, Amazonas and Roraima that the environmental indicators were more favorable, but the social and economic were deficient. The rural development, because it is multidimensional, had as its determinants variables social, economic and environmental, in which the best levels of this development were concentrated in the Eastern and Southern portions of the Brazilian Amazon, represented by the states of Rondônia, Pará and Tocantins, all currently , inserted in the agricultural frontier of production. In the West and North side were the worst levels of rural development, with the states of Acre, Amapá, Amazonas and Roraima integrating this territorial portion. Given this, a duality in the distribution of rural development was visible. Five main poles of rural development were highlighted: the Southeast of Pará, the East of Rondônia, the Center of Amazonas, the West of Tocantins and the Northeast of Pará. It was also in these poles where the largest population contingencies were verified and, therefore, confirming the initial hypothesis adopted, that is, the municipalities with the highest rural population densities presented the highest levels of rural development, including with correlation and regression analysis positive and statistically significant. It has also been observed that the main federal highways in the region (BR - 364 and BR - 153) have acted as real development corridors. Finally, we verified the existence of spatial clusters in the rural development of the region, in which six spatial patterns stood out, both high and low development, proving the second part of the hypothesis drawn. There is a pattern of heterogeneous rural development in the region, with formations of spatial agglomerates of municipalities with similar levels of rural development, such as the clusters of low rural development in Acre, Amazonas and East of Tocantins or of high development in Rondônia, Pará and West of Tocantins.